A step into the rare biosphere: genomic features of the new genus Terrihalobacillus and the new species Aquibacillus salsiterrae from hypersaline soils - Galisteo, Cristina; de la Haba, Rafael R.; Sánchez-Porro, Cristina; Ventosa, Antonio (Frontiers in Microbiology, 2023)
Hypersaline soils are a source of prokaryotic diversity that has been overlooked until very recently. The phylum Bacillota, which includes the genus Aquibacillus, is one of the 26 phyla that inhabit the heavy metal contaminated soils of the Odiel Saltmarshers Natural Area (Southwest Spain), according to previous research. In this study, we isolated a total of 32 strains closely related to the genus Aquibacillus by the traditional dilution-plating technique. Phylogenetic studies clustered them into two groups, and comparative genomic analyses revealed that one of them represents a new species within the genus Aquibacillus, whereas the other cluster constitutes a novel genus of the family Bacillaceae. We propose the designations Aquibacillus salsiterrae sp. nov. and Terrihalobacillus insolitus gen. nov., sp. nov., respectively, for these two new taxa. Genome mining analysis revealed dissimilitude in the metabolic traits of the isolates and their closest related genera, remarkably the distinctive presence of the well-conserved pathway for the biosynthesis of molybdenum cofactor in the species of the genera Aquibacillus and Terrihalobacillus, along with genes that encode molybdoenzymes and molybdate transporters, scarcely found in metagenomic dataset from this area. In-silico studies of the osmoregulatory strategy revealed a salt-out mechanism in the new species, which harbor the genes for biosynthesis and transport of the compatible solutes ectoine and glycine betaine. Comparative genomics showed genes related to heavy metal resistance, which seem required due to the contamination in the sampling area. The low values in the genome recruitment analysis indicate that the new species of the two genera, Terrihalobacillus and Aquibacillus, belong to the rare biosphere of representative hypersaline environments.